Update Tatalaksana Manajemen Luka Bakar - Muh Arsal Shiddiq K; Nurelly N Waspodo; Arwi Amiruddin (Pusat riset dan Inovasi Nasional, 2025)
Burns are one of the global health problems that still cause high morbidity and mortality rates, especially in countries with limited resources. Burn management is currently undergoing rapid development through a multidisciplinary approach that includes early resuscitation, local wound care, infection control, pain management, nutritional support, and long-term rehabilitation. This study uses the literature review method by examining articles from international databases for the period 2020–2025 to obtain the latest information on burn management updates. The results of the analysis showed that innovative therapies such as the use of stem cells, biomaterials (e.g. fish skin graft), as well as nanomedicine technology with silver nanoparticles have been proven to accelerate tissue healing and reduce complications. In addition, classic approaches such as early debridement, modern dressing selection, and enteral nutrition remain the primary basis in clinical treatment. Psychosocial and physical rehabilitation aspects are also increasingly considered because they have a significant effect on the quality of life of patients. Although various therapeutic innovations have shown promising results, translation to clinical practice still faces barriers in the form of cost, regulation, and limited facilities. Therefore, updates on burn management are needed to ensure more effective, efficient, and equitable management in modern medical practice.